2020
DOI: 10.1088/1742-6596/1442/1/012040
|View full text |Cite
|
Sign up to set email alerts
|

Preference analysis of determining jobs using conjoint analysis

Abstract: Nowadays, there are many graduates who are not directly employed after receiving bachelor’s degree. The graduates who are not employed seem largely unaware of career opportunities and unsure of how to apply their skills in the workforce. This indicates a lack of career guidance, coaching and counselling. This research aims to study people’s preferences on determining their jobs by using conjoint analysis. Four factors are evaluated: (1) income, (2) suitability of the workplace with educational background, (3) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 3 publications
0
3
1
Order By: Relevance
“…This study has been done on media and communication students who are budding journalists; they are worried about future jobs. Unlike studies done earlier, which stated that salary and benefits are the most preferred job attribute (Yasmin et al, 2016;Karima et al, 2020), and organizational reputation also being of significant importance to them (Montgomery & Ramus, 2011), our study in the pandemic situation yields results that are different. Here, the most important job attribute for students is job security.…”
Section: Discussion and Theoretical Implicationcontrasting
confidence: 86%
See 1 more Smart Citation
“…This study has been done on media and communication students who are budding journalists; they are worried about future jobs. Unlike studies done earlier, which stated that salary and benefits are the most preferred job attribute (Yasmin et al, 2016;Karima et al, 2020), and organizational reputation also being of significant importance to them (Montgomery & Ramus, 2011), our study in the pandemic situation yields results that are different. Here, the most important job attribute for students is job security.…”
Section: Discussion and Theoretical Implicationcontrasting
confidence: 86%
“…Students who expected higher pay packages (Karima et al, 2020 ) are now ready for lower packages, but want to have a source of income desperately. Therefore, it becomes important for recruitment managers to prepare themselves for the upcoming revival and hiring thereafter.…”
Section: Introductionmentioning
confidence: 99%
“…Attributes with a high importance value indicated that these attributes are more necessary than others. Besides, these attributes are important for consumers to determine their product purchases [20]. The importance values (Table 4) , including meatball elasticity (37.025%), dominant taste (18.609%), the information of nutritional value (12.930%), price (10.843%), ingredients information (10.658%), and meatball smoothness (9.934 %).…”
Section: Conjoint Analysis Resultsmentioning
confidence: 99%
“…A positive utility value at the attribute level indicates greater consumer satisfaction if the attribute level is in the product. In contrast, a negative utility value means otherwise [20]. Meatball elasticity is important and affects buying determination of customers, which the customer and Indonesian National Standard defined as springy texture.…”
Section: Conjoint Analysis Resultsmentioning
confidence: 99%